Quality of Life in Iranian Patients with Acne - H. Safizadeh; S. Shamsi-Meymandy; A. Naeimi (Dermatology Research and Practice)
Acne is a chronic inflammatory disease of pilosebaceous units. Although the acne isnot a life threatening disease, studies have revealed that it has significant effect on self-image and quality of life. The purpose of this paper was to investigate the health-related quality of life in patients with acne in an Iranian context. Dermatology Life Quality Index (DLQI) and Cardiff Acne Disability Index (CADI) were used for measuring quality of life, and severity of acne was measured by Global Acne Grading System (GAGS). The mean (±SD) of DLQI and CADI scores was 6.42 (±4.77) and 5.97 (±2.97), respectively. Acne influenced the quality of life in 51.8% of patients from moderate to very much, and the quality of life was affected by the severity of acne (P < 0.01). Since acne has significant effects on patient’s quality of life, the management of patients with acne requires more attention to different aspects of quality of life.